2022
DOI: 10.1161/circep.121.010631
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Atrioventricular Nodal Reentrant Tachycardia in Patients With Congenital Heart Disease

Abstract: Atrioventricular nodal reentrant tachycardia represents the most common regular supraventricular arrhythmia in humans, and catheter ablation of the so called slow atrioventricular nodal pathway has been effectively performed for decades. In patients with congenital heart disease, a combination of different factors makes catheter ablation of atrioventricular nodal reentrant tachycardia substrate particularly challenging, including abnormal venous access to intracardiac structures, abnormal intracardiac anatomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Hasanin & Kinsara ( 2008 ) reported the case of a 24‐year‐old soldier with syncopal attacks attributed to paroxysmal complete AV block in the setting of SA with persistent LSVC. Catheter ablation may be difficult in patients with congenital heart disease, because of potentially deviant and often unpredictable sites of the specific conduction system (Waldmann et al, 2022 ). Khairy et al ( 2007 ) reported a case of inverted AV nodal input in a 25‐year‐old patient with surgically repaired partial AV canal defect.…”
Section: Discussionmentioning
confidence: 99%
“…Hasanin & Kinsara ( 2008 ) reported the case of a 24‐year‐old soldier with syncopal attacks attributed to paroxysmal complete AV block in the setting of SA with persistent LSVC. Catheter ablation may be difficult in patients with congenital heart disease, because of potentially deviant and often unpredictable sites of the specific conduction system (Waldmann et al, 2022 ). Khairy et al ( 2007 ) reported a case of inverted AV nodal input in a 25‐year‐old patient with surgically repaired partial AV canal defect.…”
Section: Discussionmentioning
confidence: 99%